Listeriosis - Rosaler, Maxine (New York : Rosen Pub. Group, 2004)
Discusses the symptoms, effects, outbreaks, and prevention of Listeriosis, a disease caused by eating contaminated food, and examines how scientists track its source.
Listeriosis: a short history -- The spread of listeriosis -- Outbreaks --The culprits -- The need for change.
Includes bibliographical references (p. 60) and index.
Keywords: Listeriosis -- Juvenile literature; Listeriosis; Diseases; Food poisoning; Epidemics